2010
DOI: 10.1007/s10560-010-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Who Uses Formal, Early Child Care in California? A Comparative Study of Children from Immigrant and Nonimmigrant Families

Abstract: The purpose of this study is to examine the predictors of formal, early child care usage and to study the differences between immigrant and nonimmigrant families in their use of formal (center-based, preschool, Head Start, and family child care) and informal child care arrangements (grandparent and nanny) among California's children. Since the California Health Interview Survey (CHIS) had children from California's immigrant and nonimmigrant families, the data for 897 preschool age children who attended child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Few studies have carefully examined whether predictors of child care, especially for infants and toddlers, operate similarly in immigrant families as in native families. Moreover, given the great heterogeneity within immigrant families in the U.S., it is essential to understand within-group forces related to families' child care decisions emanating from factors such as parental region of origin, family economic and social resources, parental preferences, or the availability of care options in immigrant communities (Brandon, 2004;Hernandez, Denton, & Macartney, 2007a;Santhiveeran, 2010a). This study aims to fill gaps in the literature by examining patterns of infant and toddler care selection among a diverse group of children of immigrants in the U.S., using data from the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B).…”
Section: Patterns Of Infant and Toddler Ece Use In Immigrant Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have carefully examined whether predictors of child care, especially for infants and toddlers, operate similarly in immigrant families as in native families. Moreover, given the great heterogeneity within immigrant families in the U.S., it is essential to understand within-group forces related to families' child care decisions emanating from factors such as parental region of origin, family economic and social resources, parental preferences, or the availability of care options in immigrant communities (Brandon, 2004;Hernandez, Denton, & Macartney, 2007a;Santhiveeran, 2010a). This study aims to fill gaps in the literature by examining patterns of infant and toddler care selection among a diverse group of children of immigrants in the U.S., using data from the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B).…”
Section: Patterns Of Infant and Toddler Ece Use In Immigrant Familiesmentioning
confidence: 99%
“…Such differences in norms, beliefs, and practices may lead Mexican and Asian immigrant households to different childcare choices, with Asian parents more likely to enroll their children in center-based ECE programs with a more structured academic focus. Few studies of child care selection have attempted to disaggregate immigrant families by country of origin, but those that have find differential child care selection patterns based on parental homeland (Chiswick & DebBurman, 2006;Espinosa et al, 2013;Hernandez et al, 2007b;Miller et al, 2013;Santhiveeran, 2010a;Winsler, Robinson, & Thibodeaux, 2013). Comparing patterns of child care use among Asian, European, and Latino immigrant families, Santhiveeran (2010a) found that Asian families selected into relative and center-based care at the highest rates, Latino families selected into home-based care and Head Start/public prekindergarten at the highest rates, and European families used parent care at the highest rates.…”
Section: Ece Selection In Immigrant Familiesmentioning
confidence: 99%
“…Also, child care usage is linked specifically to family country of origin, regardless of ethnicity or DLL status. Mexican (and some other “Latino”) families are less likely to use center-based ECE programs, while immigrants from many Asian countries are actually more likely to use formal, center-based child care (Santhiveeran, 2010). Some have suggested that lower rates of center-based ECE services for Latino immigrants could be due more to their low-income status relative to other immigrant groups (rather than language status per se; Han, Lee, & Waldfogel, 2012).…”
Section: Child Care Use: Family and Contextual Factorsmentioning
confidence: 99%
“…The literature to date suggest that ECE enrollment decisions among Spanish-speaking DLL families may be particularly related to: 1) monetary and other constraints similar to other low-income families such as family earnings and the supply of ECE options in local communities (Delgado, 2009; Greenfader & Miller, 2014; Hernandez et al, 2011; Santhiveeran, 2010); 2) factors specific to Spanish-speaking DLL families such as country of origin, immigration status, parental fluency with English, and enrollment of other DLL families at the center (Greenfader & Miller, 2014; Hirshberg et al, 2005; Liang, Fuller, & Singer, 2000; Miller, Votruba-Drzal, & Coley, 2013; Vesely, 2013; Ward, LaChance, & Atkins, 2011); and 3) factors specific to Spanish-speaking DLL children such as the child’s Spanish and English language abilities and skills (Espinosa, 2013; Winsler et al, 2014). …”
Section: Child Care Decisions Among Spanish-speaking Dll Familiesmentioning
confidence: 99%